Digitalisasi Marketing Bagi Pelaku UMKM Kabupaten Blitar - Siti Azizah; Irfan H. Djunaidi; Diah Priharsari; Mas Ayu Ambayoen; Siti Hamidah (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of community service through this Doctoral Service Grant is to help market MSME products assisted by the Blitar Regency Livestock and Fisheries Service through the Triple-Helix model with the concept of e-commerce. The expected result is to expand the market of assisted MSME products in Blitar Regency produced by OPS Cooperative, Srikandi Kitchen, MuZa Smoked Salted Eggs and AKBest (Akademi Komunitas Negeri Putra Sang Fajar Blitar). The location of community service activities will be carried out in Blitar Regency from May to August 2022. The steps of the activity are: 1. Coordination to establish triple-helix cooperation  2. Improving the product image of MSMEs 3. Provide counseling on market share, knowing desires and recognizing potential customers 4. Providing online processed product promotion facilities 5. Providing skills about online transactions and the Canva application The result that has been obtained during the activity process is that parties in the triple-helix model can coordinate so that MSMEs are always informed of government programs. Canva application training and social media creation assistance can improve the product image of MSMEs and then also provide skills about market share, and potential consumers in addition to online transactions. The continuation of the program is still needed for assistance in order to maintain business motivation and improve product quality.